Hegemonic Femininities and Intersectional Domination. (December 2019) - Hamilton, Laura T.; Armstrong, Elizabeth A.; Seeley, J. Lotus; Armstrong, Elizabeth M.
We examine how two sociological traditions account for the role of femininities in social domination. The masculinities tradition theorizes gender as an independent structure of domination; consequently, femininities that complement hegemonic masculinities are treated as passively compliant in the reproduction of gender. In contrast, Patricia Hill Collins views cultural ideals of hegemonic femininity as simultaneously raced, classed, and gendered. This intersectional perspective allows us to recognize women striving to approximate hegemonic cultural ideals of femininity as actively complicit in reproducing a matrix of domination. We argue that hegemonic femininities reference a powerful location in the matrix from which some women draw considerable individual benefits (i.e., a femininity premium) while shoring up collective benefits along other dimensions of advantage. In the process, they engage in intersectional domination of other women and even some men. Our analysis re-enforces the utility of analyzing femininities and masculinities from within an intersectional feminist framework.